Modified protocol comparing sporicidal activity of different non-thermal plasma generating devices - Anna Machková; Leonardo Zampieri; Tomasz Czapka; Jan Hrudka; Eva Vaňková; Josef Khun; Emilio Martines; Jana Brotánková; Luigi Cordaro; Gianluca De Masi; Vladimír Scholtz (Scientific Reports)
Abstract Due to the great increase in the non-thermal plasma (NTP) bio-applications, especially thanks to its antimicrobial properties, many types of NTP generating devices have been developed recently. However, a comparison of these devices is difficult due to the differences in the setup of studies testing them, e.g., in species of microorganisms used and sample preparations. In this study, we optimized a robust and reproducible standard protocol using Bacillus subtilis spores and applied it to compare seven different NTP generating devices in terms of technical parameters and sporicidal properties. Inhibition zones determined using the Aurora software and the complete inhibition of bacteria growth induced by the NTP treatment were analyzed to determine both local and overall effects, respectively. The highest sporicidal efficacy of the tested devices was achieved by the volume dielectric barrier discharge from Wroclaw, which inhibited 99.9% of colony forming units after 30 min of exposure. To our knowledge, a comparative study of this extent has not been published to date. The presented protocol is based on an established bacterial method and can therefore serve as a general standard for an effective comparison of NTP sources across laboratories worldwide.